2010
DOI: 10.1016/j.schres.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Social skill and social cognition in adolescents at genetic risk for psychosis

Abstract: Adolescents at genetic high risk (GHR) for schizophrenia have shown social skill impairments and there is some evidence to suggest they have Theory of Mind (ToM) deficits; however no research has used a standardized, performance-based behavioral measure to assess social functioning in this population nor evaluated ToM with a well-validated measure. We evaluated the psychometric properties of a new, theoretically-derived assessment of social functioning in GHR adolescents: the "High-Risk Social Challenge" task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 30 publications
3
44
1
1
Order By: Relevance
“…35,36 These deviations may increase the probability of psychotic symptom expression, as early subclinical pathological ideas are not corrected in social interaction, resulting in even worse interpersonal functioning. 37 Breaking this cycle may be important and may offer opportunities for early intervention, 38 eg, using cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 These deviations may increase the probability of psychotic symptom expression, as early subclinical pathological ideas are not corrected in social interaction, resulting in even worse interpersonal functioning. 37 Breaking this cycle may be important and may offer opportunities for early intervention, 38 eg, using cognitive behavioral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Decades of research have established that individuals with SZ have difficulty in reading and interpreting facial emotion when compared with control subjects (e.g., [17,65,10,43]; impairments which have been demonstrated to be moderately stable over time [32,2]. Impairments in facial emotion recognition have been linked to social and occupational outcomes such as unemployment, need for assisted living [58,29], decreased social competence, conversational skills and social interest [49,30], and inappropriate personal appearance [23]. This impact of facial emotion recognition deficits is perhaps not surprising when one considers that facial emotional expressions are the building blocks of social interaction, conveying vital non-verbal cues for inferences about the motivation and intentions of others [14].…”
Section: Introductionmentioning
confidence: 99%
“…As regards ToM, a few studies have addressed this question behaviourally in the recent past. While Couture et al (2008) found that subjects at high risk for psychosis -as determined using the Structured Interview for Prodromal Symptoms (SIPS; Miller et al, 1999) -performed comparably well compared to healthy controls on a task that requires inference of complex mental states from viewing the eye region of a person in still photographs (Reading the Mind in the Eyes Task (RMET); Baron-Cohen et al, 2001), a finding that was recently replicated (Gibson et al, 2010). Chung et al (2008) showed that subjects at high risk for psychosis -as determined using the Comprehensive Assessment of At-Risk Mental States (CAARMS; Yung et al, 2005) -performed more poorly on a second-order ToM task (that is, a representation of another person's state of mind about a third person's mental processes) and an advanced ToM task compared to healthy controls, but not on a first-order ToM task (that is, a representation of another person's state of mind) or a simpler cartoon task.…”
Section: Introductionmentioning
confidence: 99%